Morning headache in sleep apnoea: clinical and polysomnographic evaluation and response to nasal continuous positive airway pressure - AĞAN YILDIRIM, KADRİYE (SAGE PUBLICATIONS LTD, 2009)
Morning headache is accepted as part of clinical findings of obstructive sleep apnoea syndrome (OSAS). The prevalence of morning headache is at variable levels from 18% to 74% in patients with OSAS. However, there is controversy over the association of morning headache and OSAS. We studied morning headache prevalance and characteristics in 101 controls with apnoea-hypnoea index (AHI) < 5 and 462 OSAS patients with AHI >= 5. Morning headache was reported by only nine (8.9%) subjects in a control group compared with 156 (33.6%) of OSAS patients (P < 0.01). Morning headache prevalance was significantly higher in severe and moderate OSAS groups. AHI was significantly higher in OSAS patients with morning headache compared with patients without morning headaches. Oxygen saturation nadir during rapid eye movement and non-rapid eye movement sleep as well as mean oxygen saturation value during total sleep time were also found to be significantly lower in morning headache group. However, none of the sleep parameters was found to be determinants of morning headache. Morning headache was more frequently reported by patients of female gender and with primary headache history. Morning headache was totally resolved in 90% of patients treated with nasal continuous positive airway pressure. The history of OSAS should be considered in the differential diagnosis of morning headache.
Keywords: Obstructive sleep apnoea syndrome; morning headache; continuous positive airway pressure